Weakly bound halo breakup of neutron- Li 7 and nucleon- Be 7 on a lead target - Mukeru, B.; Frederico, T.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2020)
A comparative analysis of the breakup cross-sections, using continuum discretized coupled-channel approach, is presented for the weakly bound p-wave neutron-Li7 and nucleon-Be7 projectiles on the Pb208 target, by investigating the role of interaction effects between the core (Li7, Be7) with the target. The extra charge in the B8 has the effect to increase the Coulomb contribution in the breakup reaction channel. By fixing both projectile ground-state binding energies at 0.137 MeV (B8 experimental one), with incident energies at the Coulomb barrier and above, we found that the charge difference accounts for over 30% of the neutron-Be7 breakup cross sections, substantially larger than the corresponding one for proton-Be7. The large enhancement of the neutron-halo breakup cross-section with respect to the proton-halo case shown in this work is associated to dynamical effects coming from the excitation of the projectile internal continuum due to the nucleon-target and core-target interactions, together with the widely accepted static effects coming from the long wave-function tail of the weakly bound neutron. The interplay between these dynamical and static effects in the energy spectrum of the B8 fragments is visible, revealed by the peak of the energy distribution pushed to higher relative energies. This follows from the two-body final state interactions between the charged fragments distorted by the three-body reaction environment.